REGULATING THE CONVERSION OF CONVENTIONAL BANKS TO ISLAMIC: THE 4 QUADRANTS CONVERSION (4-QC) FRAMEWORK - Suleiman Sani; Ashurov Sharofiddin; Mustapha Abubakar (Bank Indonesia, 2023)
This research paper proposes a framework for converting conventional banks to full-fledged Islamic banks as a catalyst for propelling the Islamic finance industry to Islamic Finance 2.0 by addressing the paucity of a regulatory framework for Central Banks to regulate this conversion. To address this, the paper proposes the â€œ4Quadrants Conversion (4-QC) Frameworkâ€ as a model framework for Central Banks to regulate the conversion process, consisting of twentyfour components classified into four quadrants. The proposed conversion involves leaving Shariâ€™ah non-compliant activities and adopting Shariâ€™ah permissible alternatives. This paper adopts a qualitative research method based on content analysis. The research findings suggest that the proposed regulatory framework can facilitate the successful conversion, resulting in a dual result of creating new Shariâ€™ah-compliant entities and eliminating non-compliant entities. The proposed regulatory framework can also guide banks to plan, implement, and self-assess their progress to ensure a timely and less cumbersome conversion.